Millennials' Preferences for Investing in Sharia Mutual Funds on the Bibit Application - Rahma Mutiara Dewi; Kurniawan, Muhammad; Mutiasari Nur Wulan (Al-Mashrof: Islamic Banking and Finance, 2025)
This study aims to determine the effect of financial capability, product knowledge and religiosity on millennials' interest in investing in Islamic mutual funds in the bibit application. The type of research used is quantitative research. The population in this study is the millennial generation aged 23 to 42 years old who live in Bandar Lampung City and know the bibit application and have income, in this case the population totals 96 people. The sampling technique in this study used purposive sampling. Data collected using an online questionnaire via google form. The results showed that financial capability and religiosity had a positive and significant effect on the millennial generation's interest in investing in Islamic mutual funds in the bibit application. Meanwhile, product knowledge does not significantly affect the interest of the millennial generation in investing in Islamic mutual funds in the bibit application. Keywords: Millennial Generation, Investment Interest, Financial Capability, Product Knowledge, Religiosity